Austria's post-Holocaust Jewish community: a subaltern counterpublic between the ethics and morality of memory - Karner, Christian (Palgrave Macmillan, 2015)
In The Ethics of Memory, Avishai Margalit argues that memory and ethics are features of the ‘thick relations’ that bind ‘families, clans, tribes, religious communities and nations’ internally. This he contrasts to the ‘thin relations’ that connect humanity as a whole and that are generally not underpinned by universal investments in a shared past. There are exceptions, however: genocide and, paradigmatically, the Holocaust present a moral case for a universal memory.